2020
DOI: 10.1038/s41598-020-79066-8
|View full text |Cite
|
Sign up to set email alerts
|

Ocean acidification may be increasing the intensity of lightning over the oceans

Abstract: The anthropogenic increase in atmospheric CO2 is not only considered to drive global warming, but also ocean acidification. Previous studies have shown that acidification will affect many aspects of biogenic carbon uptake and release in the surface water of the oceans. In this report we present a potential novel impact of acidification on the flash intensity of lightning discharged into the oceans. Our experimental results show that a decrease in ocean pH corresponding to the predicted increase in atmospheric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 37 publications
2
15
0
Order By: Relevance
“…The multivariate linear fit model of LFI as a function the experimental conditions of salinity, pH and TA, yields significant fits for pH and TA and non-significant for salinity (Figure 2). Furthermore, the leverage residuals for LFI indicate a significant positive relation with TA as expected [14], a significant negative relation of LFI with pH as expected [13] and an unexpected negative yet insignificant relation with salinity [12]. It should be noted that in the Asfur [12] study, the dependence of LFI on salinity was established for a NaCl solutions with increasing concentration (0-7 g/L).…”
Section: Resultssupporting
confidence: 74%
See 4 more Smart Citations
“…The multivariate linear fit model of LFI as a function the experimental conditions of salinity, pH and TA, yields significant fits for pH and TA and non-significant for salinity (Figure 2). Furthermore, the leverage residuals for LFI indicate a significant positive relation with TA as expected [14], a significant negative relation of LFI with pH as expected [13] and an unexpected negative yet insignificant relation with salinity [12]. It should be noted that in the Asfur [12] study, the dependence of LFI on salinity was established for a NaCl solutions with increasing concentration (0-7 g/L).…”
Section: Resultssupporting
confidence: 74%
“…These conclusions were based on laboratory generated electrical sparks that were discharged into the experimental solutions as detailed in the methods section below. Based on these experiments it was shown that the Lightning Flash Intensity (LFI) in our experimental setup, is positively correlated with the concentration of NaCl in de-ionized water solutions [12], negatively correlated with the pH and positively correlated with the TA of LS seawater of [13,14]. The salinization and corresponding increase in TA due to the AHD and increased evaporation due to global warming, coupled with the ongoing process of OA in the LS could have caused lightning intensity in this region to increase.…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations